2015
DOI: 10.1002/jcb.25199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Novel ncRNA Molecules, p15‐piRNAs, on the Methylation of DNA and Histone H3 of the CDKN2B Promoter Region in U937 Cells

Abstract: Non-coding RNAs (ncRNAs) play key roles in epigenetic events. However, the exact mechanism of ncRNA guidance, particularly piwi-interacting RNAs (piRNAs), for the targeting of epigenetic regulatory factors to specific gene regions is unclear. Although piRNA function was first established in germ-line cells, piRNA may be crucial in cancer cells. This study investigated the potential roles of CDKN2B-related piRNA in leukemia cells to provide a potential tumorigenesis model of leukemia. CDKN2B-related piRNAs, hsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…There are increasing numbers of reports revealing the modulation of H3K9 methylation by ncRNAs. For example, p15-piRNAs can recruit SUV39H1 for H3K9me3 accumulation on the CDKN2B promoter (Wu et al, 2015a), and Air ncRNA can recruit EHMT2 for H3K9me2 establishment on imprinted genes (Nagano et al, 2008). To our knowledge, the ncRNAs required for H3K9 demethylation by the KDM4 family are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing numbers of reports revealing the modulation of H3K9 methylation by ncRNAs. For example, p15-piRNAs can recruit SUV39H1 for H3K9me3 accumulation on the CDKN2B promoter (Wu et al, 2015a), and Air ncRNA can recruit EHMT2 for H3K9me2 establishment on imprinted genes (Nagano et al, 2008). To our knowledge, the ncRNAs required for H3K9 demethylation by the KDM4 family are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PIWIL1–piRNA-DQ593109 complexes were overexpressed in glioma endothelial cells, and increased blood–tumor barrier permeability by regulating the lncRNA maternally expressed-3 (MEG3)/miR-330-5p/runt-related transcription factor-3 (RUNX3) regulatory loop 110. In leukemia cells, overexpression of CDKN2B-related piRNA hsa_piR_011186 promoted cell-cycle progression and inhibited apoptosis 111. These effects were probably mediated by the piRNA complex of cyclin-dependent kinase inhibitor-2B (CDKN2B)-related piRNA that were associated with DNMT1 and/or enhancer of zeste homolog-2 (EZH2) to modulate the methylation of DNA and H3 in the promoter region of the CDKN2B gene, highlighting epigenetic modifications on the promoter of cell-cycle regulating gene 111.…”
Section: Pirnas In Cancermentioning
confidence: 99%
“…In leukemia cells, overexpression of CDKN2B-related piRNA hsa_piR_011186 promoted cell-cycle progression and inhibited apoptosis 111. These effects were probably mediated by the piRNA complex of cyclin-dependent kinase inhibitor-2B (CDKN2B)-related piRNA that were associated with DNMT1 and/or enhancer of zeste homolog-2 (EZH2) to modulate the methylation of DNA and H3 in the promoter region of the CDKN2B gene, highlighting epigenetic modifications on the promoter of cell-cycle regulating gene 111. Several piRNAs were aberrantly expressed in testicular germ cell tumors (TGCTs).…”
Section: Pirnas In Cancermentioning
confidence: 99%
“…Illustrated in Figure 1, methylation inhibits binding of transcription factors to promoters in diverse ways: long noncoding RNAs (lncRNAs) can interact with EZH2, which in turn recruits DNMTs to facilitate DNA methylation at target sites [52] and, conversely, some lncRNAs inhibit DNA methylation by inhibiting DNMT binding to CpGs [53]; Piwi-interacting RNAs (piRNAs) can associate with DNMT1 to target methylation at promoter regions [54,55]; methyl-CpG binding proteins (MBPs) contain methyl-CpG binding domains (MBDs), decipher methylated DNA by binding to methylated CpGs, and complex with HDAC and other MBPs that remodel chromatin and repress transcription [56]; and, the transcriptional repressor CCCTC-binding factor (CTCF) manipulates the 3D structure of chromatin to promote and repress gene expression at various sites and is inhibited by CpG methylation [57].…”
Section: Mechanisms Of Promoter Methylation Mediated Gene Silencingmentioning
confidence: 99%